Participatory Monitoring and Evaluation of Ebola Response Activities in Lofa County, Liberia: Some Lessons Learned - Hassaballa, Ithar; Fawcett, Stephen; Sepers, Charles; Reed, Florence DiGennaro; Schultz, Jerry; Munodawafa, Davison; Phori, Peter M; Chiriseri, Ephraim; Kouadio, Koffi (SAGE Publications Inc., 2021)
To address the Ebola outbreak in West Africa, the World Health Organization and the United Nations Children’s Fund led a multilevel and multisectoral intervention known as the Ebola response effort. Although surveillance systems were able to detect reduction in Ebola incidence, there was little understanding of the implemented activities within affected areas. To address this gap, this empirical case study examined (a) implementation of Ebola response activities and associated bending the curve of incidence of Ebola virus disease and (b) candidate factors associated with fuller implementation of the Ebola response effort. A mix of qualitative and quantitative methods were used to address these questions. A participatory monitoring and evaluation system was used to capture, code, characterize, and communicate nearly a hundred Ebola response activities implemented in Lofa County, a highly affected area in Liberia. The Ebola response effort was enabled by community engagement and collaboration across different sectors. Results showed fuller implementation corresponded with a marked reduction in Ebola virus disease. This report concludes with a discussion of how monitoring and evaluation can strengthen implementation of activities needed to address disease outbreaks.